Resveratrol reverses the adverse effects of a diet-induced obese murine model on oocyte quality and zona pellucida softening. Issue 5 (23rd April 2018) - Jia, Zhenzhen; Feng, Zeyang; Wang, Lining; Li, Hao; Wang, Hongyu; Xu, Dingqi; Zhao, Xin; Feng, Daofu; Feng, Xizeng
Abstract : Resveratrol exerts protective effects on ovarian injury, decreased oocyte quality and zona pellucida softening due to obesity. Abstract : Reproductive dysfunction associated with obesity is increasing among women of reproductive age, including infertility and increasing risk of miscarriage. In females, reproductive disorders are linked to declining quality of oocytes. Using a model of diet-induced obesity, we have investigated the possible effects of obesity on oocyte quality, including metabolism, lipid accumulation, ROS levels, meiosis and changes in spindle structure in Metaphase II. Our study showed that obesity induced by a high fat diet can impair oocyte meiosis, destroy spindle assembly, and promote oxidative stress and abnormal mitochondrial distribution. With the addition of resveratrol, the negative impact of diet-induced obesity on the quality of oocytes was alleviated to some extent. In addition, we found that obesity causes mouse oocytes to soften, and resveratrol can restore the zona pellucida of oocytes to the same state as the control group. In conclusion, resveratrol can reverse the adverse effects of obesity on oocytes, which is beneficial for subsequent embryonic development.